Cognitive Learner Engagement Compared between EFL Course Delivery Modes - Sampson, Andrew E. (Linguarum Arena, 2023)
The quasi-experimental classroom study reported in this paper compared the eff ectiveness of three adult EFL course delivery modes – face-to-face group classes, one-to-one private tutoring and online selfstudy – by analysing learners’ cognitive engagement, understood as the level of participation, involvement and eff ort of learners in each mode as they completed the same language tasks. The study was conducted within a Vygotskian sociocultural theoretical framework in which language serves as a mediational tool in dyadic interaction and also as a means of cognitive selfregulation in inner speech during independent study. Data included the transcribed talk of learner-learner and learner-teacher dyads, and think-aloud protocols produced by online self-study learners. These were analysed both quantitatively and qualitatively for the presence of Language-Related Episodes (LREs), instances in which learners talk about the language they are producing and other- or self-correct. Each LRE was then further analysed for evidence of limited cognitive engagement, where linguistic preferences were stated without further deliberation, or elaborate cognitive engagement, where there was evidence of a cognitive self-regulation strategy. Results suggest that elaborate cognitive engagement, evidenced in episodes where participants notice and refl ect on language forms, test hypotheses, generate rules or options from which to choose, and seek or provide justifi cations, occurs to a similar extent in face-to-face group classes, oneto- one private tutoring and online self-study. Task design appears to aff ect cognitive engagement, with most instances of engagement in the formfocussed passage editing task being elaborate rather than limited, while a greater prevalence of limited engagement was observed in the meaningfocussed written composition. Slightly less limited engagement was observed in one-to-one tuition, where teachers tended to “add” elaborate engagement to episodes which would otherwise have displayed limited engagement only. That elaborate engagement characterised LREs to a similar extent between teacher-learner and learner-learner dyads suggests that a teacher is not required in dyadic interaction for elaborate cognitive engagement to occur. Learners in student-student dyads in group classes talk to test hypotheses and generate options and justifi cations, although their dialogue tends to be less interrogative of each other than teacher-learner talk. This fi nding adds to the considerable body of work that supports peer interaction as an opportunity for learners to experiment with language and debate form and meaning. Learners studying in group classes therefore appear to benefi t from cognitive engagement that is quantitively, albeit not qualitatively, comparable to private tuition contexts. In peer-peer interaction, the prominence of LREs characterised by limited engagement in one learner and elaborate engagement in the other suggests it is unnecessary for both participants to be elaborately engaged for episodes to be languaged and resolved. This suggests that dyadic interaction that is asymmetrical in terms of cognitive engagement is not necessarily a problem for teachers to address. While asymmetric interaction has been previously observed in the literature in one-to-one tuition, and also in the higher proportion of teacher-engaged episodes in the one-to-one mode in the present study, the fi nding that asymmetricity in cognitive engagement is also a feature of learner pairwork is a novel contribution of the present study to the engagement literature.